As Crianças da Ponte: o trabalho de crianças e adolescentes no comércio fronteiriço de Foz do Iguaçu Paraná - Reimann, Valdirene (2013)
The Foz do Iguaçu and Ciudad Del Este/ Paraguay border is a place where many visitants circulate, there s a large flow of capitals and merchandise. At the marketing relationship interfaces of the border trades hides degrading forms of work that helps maintain the activity profitability, for example, the childhood work exploration. Investigating Foz do Iguaçu s past after the Itaipu s hydroelectric plant was built, it s possible to understand the emergence of a heterogeneous society, disputatious, where thousands of families survive due to the informal work commerce at de Friendship Bridge. Cultural issues have assumed great importance in order to understand childish work as a social representation part in social risk families, because they face it as a disciplinarian element and as a learning process to children. The qualitative research enables important conclusions, such as the Paraguayan nationality of the Friendship Bridge s childhood workers, the strategies and astuteness applied by these social fellows and the needing of a precocious work to complement the family income. The childhood work s consequences are worrying, reaching the kids physical and emotional health, beyond depriving them of their time assign to studies and leisure. Investigate the children and teenagers workers used mechanisms at the border commerce, understand the reasons that took them to be early incorporated at this activity and identify the social programs made to attend to these people is the purpose of this research.